Tantangan dan Peluang Pengembangan Sumber Daya Manusia di Desa Cileleuy - Yahya Muhidin; Agus Afandi; Shabri Fauza A; Nada Naurah P A; Rizkyanti Rizkyanti (PPIMAN Pusat Publikasi Ilmu Manajemen, 2025)
This research aims to analyze the challenges and opportunities in developing human resources in Cileuleuy Village, Cigugur Sub-district, Kuningan Regency, West Java Province. Using a multidisciplinary approach, this research explores various factors that influence human resource development in the village, including religious, educational, health, economic, and socio-cultural aspects. Data was collected through survey methods, in-depth interviews, and participatory observation. The results show that while there are significant challenges such as limited access to education and employment, there are also opportunities that can be utilized through local capacity building, agricultural innovation, and the development of a local culture-based tourism sector. Recommendations include human resource development strategies based on local potential and collaboration between the government, community and private sector to create a conducive environment for sustainable village development.